ETNOPEDAGOGY DALAM MEMBENTUK KARAKTER SISWA PADA PENDIDIKAN BERBASIS MADRASAH - Ade Irfan (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This study aimed to determine the role of ethnopedagogy in shaping the character of students in madrasah based education in Aceh. Etnopedagogy is Aceh's cultural values from local wisdom delivered by teachers who play a role in shaping the character of students. This research used qualitative approach with descriptive-naturalistic research type. Research subjects were madrasah teachers in Lhokseumawe City. The main instrument in this study was a researcher, while supporting instruments, namely; (1) Interview Guides, (2) Observation Sheets, and (3) Field Listing sheets. Examination of data validity in this research usesd source triangulation technique. Based on the results of the research, it was known that ethnopedagogy in shaping the character of madrasah students is done by the teacher through reading prayer before studying, reading prayer after studying as well as with madja. Hadih madja in this case is the advice given by teachers in the Acehnese language is typical and a guide of life for students.